DACODE: Distributed adaptive communication framework for energy efficient industrial IoT-based heterogeneous WSN - Junsuk Oh; Donghyun Lee; Demeke Shumeye Lakew; Sungrae Cho (ICT Express, 2023)
As the cornerstone of IoT-based systems, WSN connecting a wide range of intelligent sensor nodes is expected to bring significant changes in the near future. Due to the limited battery capacity of the sensor node, WSN considers maximizing network lifetime by minimizing the power consumption to be the most important challenge. To this end, we propose a Distributed Adaptive Communication with On/Off switching and Dual queuing for Energy efficiency (DACODE) as a novel asynchronous duty cycling mechanism. The performance evaluation shows that the proposed mechanism significantly reduces power consumption while maintaining network throughput and guaranteeing data urgency and queue stability.